Meningkatkan Kecerdasan Spiritual Melalui Cerita Bergambar pada Anak Usia Dini - Yurniawati, Yurniawati (ALAYYA : Jurnal Pendidikan Islam Anak Usia Dini, 2021)
Abstract The results of this study indicate that the low spiritual intelligence of children in group B in PAUD Al-Muttaqin Dusun Tanah Periuk, solving the problem of low spiritual intelligence of children is through picture story book learning media. After going through picture stories, the spiritual intelligence abilities of group B children in PAUD Al-Muttaqin Dusun Tanah Periuk increased. This research was conducted (2) two cycles of 15 children. Each cycle consists of 1 meeting. Each cycle consists of planning, implementation, observation, and reflection. The use of field data uses observation sheets in the form of BB (Not Developed), MB (Starting To Develop), BSH (Developing As Expected) and BSB (Developing Very Well) and documentation. The data collection was carried out to determine the ability of spiritual intelligence through the media of illustrated stories. Based on the results of the study, it was shown that through illustrated stories increased the spiritual intelligence of group B children in PAUD Al-Muttaqin Dusun Tanah Periuk. This can be seen at the meeting in Cycle 1, the percentage of children's average score from 27% increased to 46% and in Cycle II, there was a high increase as seen from the average score of children experiencing an increase of 76%. This can be said to be successful because it has reached the indicator 75% success. So through illustrated stories in improving the spiritual intelligence of children in group B in PAUD Al-Muttaqin Dusun Tanah Periuk which has been achieved and the formulation of the problem Is through illustrated story media can increase the spiritual intelligence of children group B in PAUD Al-Muttaqqin Dusun Tanah Periuk District piece of land has been solved. keyword: Early childhood, Spiritual Intelligence, Picture Story Media